Developing Interpersonal and Intrapersonal Soft Skills through School Culture at SMK Muhammadiyah Berbah - Faizal Dwi Darmawan (Insight School Academy, 2026)
Introduction to The Problem: The negative stigma surrounding Vocational High Schools (SMK) as analternative educational choice remains a challenge in the process of character formation and soft skilldevelopment among students. This condition requires schools to provide various programs capable ofdeveloping intrapersonal and interpersonal skills in a balanced manner.Purpose: This study aims to describe the implementation of soft skill development programs at SMK Muhammadiyah Berbah through religious habituation, school entrepreneurship practices, and self-reflection activities, as well as to identify the obstacles encountered in their implementation.Design/methods/approach: This study used a qualitative approach with a case study design. Data were obtained through in-depth interviews, observation, and documentation, with an Islamic Religious Education teacher as the key informant. Data analysis was carried out through data reduction, data display, and conclusion drawing.Findings: The results show that: (1) religious habituation carried out through morning greetings, assemblies, congregational Dhuha prayers, and hadith readings was able to build students’ discipline, responsibility, and self-control; (2) the management of the mini bank and school cooperative provided space for students to develop communication, cooperation, responsibility, negotiation, and entrepreneurial skills; and (3) monthly religious gatherings accompanied by written reflection contributed to increased self-awareness and behavioral evaluation among students. However, the strong communal culture among students led some of them to complete reflection tasks collectively, so that the development of intrapersonal skills had not yet occurred optimally. The handling of students with behavioral issues was carried out through coordination between guidance and counseling teachers, homeroom teachers, student affairs staff, and parents. This study found that the communal culture within the school environment plays a paradoxical role: supporting the development of interpersonal skills while potentially hindering the development of intrapersonal skills if not balanced with coaching strategies that encourage reflection and individual independence. These findings contribute to enriching the understanding of soft skill development through school culture and religious habituation among students.